Pengembangan Inovasi Produk Berbasis Social Media Listening pada Industri Korek Api Tradisional - Wahyu Purno Irawan; Abdul Chamid (CV. Kalimasada Group, 2026)
This study examines how social media listening drives product innovation in traditional manufacturing small and medium enterprises (SMEs). Using a qualitative single-case study approach, data were collected through in-depth interviews, participant observations, and document analysis at PT. Lintas Cindo Bersama, an Indonesian traditional match manufacturing company. The findings reveal that social media listening functions as a sensing mechanism within dynamic capabilities, enabling the identification of consumer insights that inform product development decisions. The translation of digital insights into product specifications requires active leadership mediation as a boundary-spanning mechanism between marketing and production divisions. Heritage-infused innovation emerged as a distinctive strategy, balancing product novelty with brand identity preservation. The study demonstrates that resource constraints do not preclude innovation when digital platforms are strategically leveraged. This research extends open innovation and dynamic capabilities theories into an underexplored context of low-involvement traditional manufacturing in developing economies. Managerial implications suggest that SMEs should integrate social media listening with production functions rather than isolating it within marketing units.